Predicting Japanese Students’ English Communication Apprehension through Learning Motivation and Willingness to Communicate - Catre, Madel (Journal of Interdisciplinary Perspectives, 2025)
Japanese students exhibit the highest levels of communication apprehension compared to other Asian countries, struggling with the worry and fear of using English. This quantitative descriptive- correlational study investigated how communication apprehension when speaking English is influenced by students’ English learning motivation and willingness to communicate. Conducted in two public high schools in Ehime Prefecture involving 230 students, the research employed purposive-quota sampling and utilized three adapted questionnaires. The findings revealed that students exhibit moderate to high motivation to learn English, driven mainly by a desire to engage with the international community. They also demonstrated different willingness to communicate in the target language, which was which was affected mainly by the level of familiarity with other participants in the conversation. They show moderate communication apprehension when speaking in English, exhibiting high apprehension in public speaking settings. Further, a significant negative correlation was found between willingness to communicate and communication apprehension. This indicates increased willingness to communicate is associated with reduced English speaking apprehension. At the same time, English learning motivation alone does not significantly impact apprehension. The study concludes that fostering willingness to communicate is crucial for reducing communication apprehension, suggesting further research to explore additional variables impacting communication apprehension.